Crimean-Congo hemorrhagic fever virus clades V and VI (Europe 1 and 2) in ticks in Kosovo, 2012. - Kurtesh Sherifi; Daniel Cadar; Skender Muji; Avni Robaj; Salih Ahmeti; Xhevat Jakupi; Petra Emmerich; Andreas Krüger (Public Library of Science (PLoS), 2014)
Despite being a small country, Kosovo represents one of the few foci of Crimean-Congo hemorrhagic fever (CCHF) in Europe. The distribution of Kosovar tick vectors and the evolution of CCHF virus in ticks are both as yet unknown. A better description of the extent and the genetic diversity of CCHFV in ticks from endemic settings is essential, in order to be controlled. We investigated the 2012 distribution of Kosovar ticks alongside the prevalence and the phylogeography of tick-derived CCHFV. Hyalomma marginatum dominated in the endemic municipalities with 90.2% versus 24.3% in the non-endemic regions. Of 1,102 tested ticks, 40 (3.6%) were CCHFV-positive, belonging to H. marginatum (29), Rhipicephalus bursa (10), and Ixodes ricinus (1). The virus strains clustered with clade V and VI related sequences. They fell into two lineages: Kosovo I and II. Kosovo I comprised strains recovered exclusively from R. bursa ticks and was closely related to AP92 prototype strain. Kosovo II clustered into Kosovo IIa, including human-derived strains, and IIb including only strains detected in H. marginatum and I. ricinus. Our phylogeographic reconstruction suggests two temporally distinct CCHFV introductions: the most probable location of the most recent common ancestor of Kosovo I lineage was in Greece (63 years ago) and that of lineages IIa-b in Turkey (35 years ago). After each CCHFV introduction into Kosovo, subsequent lineage expansions suggest periods of in situ evolution. The study provides the first insight into the genetic variability and the origin of CCHFV in ticks from Kosovo. Our findings indicate the spreading of CCHFV to non-endemic areas, which underlines the importance of further studies in order to monitor and predict future CCHF outbreaks in Kosovo. The AP92-like strains appear to be more widespread than previously thought and may provide a promising target for experimental studies due to their assumed low pathogenicity.